A Brief Survey on Six-Degree-of-Freedom Modeling for Air-breathing Hypersonic Vehicles ⁎. Issue 1 (2018) - Sachan, Kapil; Padhi, Radhakant
Abstract: The six-degree-of-freedom (six-DOF) modeling of air-breathing hypersonic vehicles (AHVs) is highly complex due to the variable flight conditions, structural elasticity and inherent aero-propulsive coupling. However, considering different modeling approaches, a significant amount of work has been reported in the area of AHV modeling. The aim of this paper is to investigate the six-DOF modeling of AHVs reported in the literature. Next, owing to the modeling uncertainties and coupled dynamics, state-of-the-art robust adaptive control design techniques have been presented for these models, which are also briefly reviewed in this paper. This survey also contains a small discussion on possible future advancements in the modeling and control of these vehicles.